Telemedicine intervention for the management of Type 2 Diabetes Mellitus: a systematic review - Soe, May Khin Soe; Wan Rushdi, Wan Muhammad Irfan; Kamaruddin, Muhammad Aqil; Mazlan, Muhammad Aliff Najman (CR Subscription Agency, 2024)
Introduction: The global prevalence of Type 2 Diabetes Mellitus (T2DM) is a significant health concern, with projections indicating a continual rise. In Malaysia, T2DM is the predominant form of diabetes, contributing to a substantial burden on public health. Poor glycaemic control and associated complications further accentuate the challenges in managing T2DM. Effective interventions are crucial, and various strategies, including selfmanagement education, peer support, and lifestyle modifications, have shown promise. Telemedicine, defined by the World Health Organization, has emerged as a transformative paradigm in healthcare, particularly in managing chronic conditions like T2DM. This research aims to conduct a comprehensive systematic review to elucidate the effects and utility of telemedicine interventions in T2DM management. The findings have the potential to inform healthcare policies and practices, guiding future research initiatives and innovations in telemedicine and chronic disease management. Methodology: This systematic review complied with the PRISMA guidelines. A comprehensive literature search was performed in PubMed, Scopus, Cochrane Library, Google Scholar, and through the application of the snowball technique. The retrieved articles were screened independently by two authors according to the eligibility criteria at different stages, including title, abstract, and full text. The potential for bias in the studies included was evaluated separately by two authors using the Joanna Briggs Institute critical appraisal tool. The data from all the articles that were included were extracted using a designated template. Results: The comprehensive review of eight studies consistently showed a low risk of bias, reflected in highly positive responses to the JBI tool. Both randomized controlled trials (RCTs) and quasi-experimental studies were meticulously evaluated, highlighting the reliability of research designs. Conclusion: The positive findings suggest that telemedicine has the potential to contribute to enhanced glycaemic control,